ANALISIS KETEPATAN KODE DIAGNOSIS PASIEN RAWAT JALAN PADA POLI SARAF DI RSUD DR. RASIDIN PADANG - Siti Handam Dewi; Rahmadhani Rahmadhani; Arif Prima; Satrio Bhagas Yudhanto; Siti Nur Hawa (Ensiklopedia of Journal, 2026)
The clarity of diagnosis writing is an important factor in coding determination. One of the issues found is the illegibility of diagnoses and the lack of completeness in filling out medical resumes, which is caused by the use of terminology in Indonesian and abbreviations that do not conform to standard norms, making it difficult for coders to read and interpret the diagnoses. The research aims to examine the accuracy of the diagnostic codes for outpatient patients in the neurology clinic. The type of research used is quantitative with a cross-sectional method, conducted at the Dr. Rasidin General Hospital in Padang. The research population consists of 532 medical record files, and the sample taken amounts to 84 outpatient medical record files using simple random sampling techniques. The type of research used is quantitative with a cross-sectional method, conducted at the Dr. Rasidin General Hospital in Padang. The research population consists of 532 medical record files, and the sample taken amounts to 84 outpatient medical record files using simple random sampling technique. The research was conducted using observations and a checklist, as well as univariate analysis. Data processing includes editing, coding, tabulation, and data cleaning. The research results indicate that out of 84 medical record files, 28 (33.3%) had unclear diagnoses due to illegible handwriting, 34 (40.5%) were incomplete due to time constraints, and 26 (31.0%) had incorrect codes due to the ambiguity and incompleteness of the diagnosis writing. The ambiguity and incompleteness of diagnosis writing affect the accuracy of coding. In the future, it is hoped that diagnosis writing will adhere to ICD-10 guidelines to facilitate the assignment of diagnosis. Keywords: Code Accuracy, Pattient Diagnosis,Outpatient Care